PENERAPAN STARTEGI DRECTED READING ACTIVITY (DRA) UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN SISWA KELAS IV SDN 025 KAWELAAN KABUPATEN POLEWALI MANDAR - Murni; Andi Adam; Desy Ayu Andhira (STKIP Subang, 2025)
This study aims to improve the reading comprehension skills of fourth-grade students at SDN 025 Kawelaan, Polewali Mandar Regency, through the implementation of the Directed Reading Activity (DRA) strategy. The type of research used is Classroom Action Research (CAR), conducted in two cycles, each consisting of planning, action implementation, observation, and reflection stages. The research subjects were 25 fourth-grade students in the 2024/2025 academic year. Data collection techniques included tests and observations, with assessment instruments in the form of activity observation sheets and learning outcome tests. The collected data were analyzed using both qualitative and quantitative methods. The results of the study indicate that the application of the Directed Reading Activity (DRA) strategy successfully enhanced students' reading comprehension skills. In the first cycle, only 10 students (40%) achieved scores above the Minimum Mastery Criteria (KKM), while 15 students (60%) remained below the standard. After improvements were made in the second cycle, all students (100%) exceeded the KKM, demonstrating significant progress. Moreover, observation results showed positive development in students' ability to comprehend reading texts. While in the first cycle, several students still struggled with understanding the content, by the second cycle, most students had shown comprehension in line with the assessment indicators. The implementation of the Directed Reading Activity (DRA) strategy is therefore effective in improving reading comprehension skills among fourth-grade students at SDN 025 Kawelaan, Polewali Mandar Regency.